HISTO-PATHOLOGICAL CORRELATION BETWEEN SENTINEL LYMPH NODE BIOPSY AND AXILLARY LYMPH NODE BIOPSY IN PATIENTS WITH CARCINOMA OF BREAST - Sonawane, Satish; Garg, Mudit (International Journal of Clinical and Biomedical Research, 2017)
Introduction: The present study was aimed at mapping of lymphatic passage of sentinel lymph node in patients of carcinoma of breast and to correlate pathology of Sentinel lymph node biopsy (SLNB) and Axillary Lymph node Dissection (ALND). Material and methods: Patients presenting with palpable breast carcinoma without clinically palpable or suspicious axillary lymph nodes, potentially curable breast carcinoma (T1, T2 tumours) who were undergoing ALND and willing to participate in the study were included in the study. Patients with prior axillary operations, large & locally advanced invasive breast cancers, ductal carcinoma in situ, prior breast surgery, prior chemotherapy, distant metastases and pregnant women were excluded from the study. The histopathology of SLNB and ALND were correlated in the patients and sensitivity and specificity of SLNB was calculated. Results: 50 patients were included in the study. The blue staining sentinel lymph node was identified in 30 of 50 (60%) procedures. Of the 30 patients in whom SLN was identified, 1(3.33%) had histologically negative nodes and 29(96.66%) had histologically positive nodes; of 20 patients who had negative sentinel nodes, 19(95%) had histologically negative evidence of axillary metastasis, while 1(5%) showed histologically positive evidence of axillary metastasis. The sensitivity of sentinel lymph node status with comparison to the gold standard i.e., histopathology report, was 96.6% while the specificity was 95%. The overall positive and negative predictive values were 96.67% and 95%, respectively. Conclusion: Although further studies are requires to confirm the findings of the present study, the SLN accurately reflects the status of axillary lymph nodes in most patients with breast cancer, and for those with early stage disease it is rapidly emerging as an alternative to conventional axillary dissection. Key words: Carcinoma Breast, Histopathology, Mapping, Axillary Lymph node Dissection, Sentinel lymph node biopsy